Clinical and Renal Biopsy Findings Predicting Outcome in Renal Thrombotic Microangiopathy: A Large Cohort Study from a Single Institute in China - Xiao-Juan YU; Feng YU; Di Song; Su-Xia Wang; Yan Song; Gang Liu; Ming-Hui Zhao (The Scientific World Journal)
Objective. The current study aimed to investigate the spectrum of etiologies and associated disorders of renal biopsy-proven thrombotic microangiopathy (TMA) patients. Methods. The clinical, laboratory, and renal histopathological data of patients with renal TMA from 2000 to 2012 in our institute were collected and reviewed. Results. One hundred and nine TMA patients were enrolled in this study. The mean age was 34.0 ± 11.1 years. Seventy patients (64.2%) were male and thirty-nine patients (35.8%) were female. There were eight patients (7.3%) with hemolytic uremic syndrome (HUS). Sixty-one patients (56.0%) were secondary to malignant hypertension. Fourteen patients (12.8%) were pregnancy-associated TMA. Other associated disorders included 17 patients with connective tissue disorders, 2 patients with hematopoietic stem cell transplantation, 4 patients with Castleman’s disease, 1 patient with cryoglobulinemia, and 2 patients with glomerulopathy. During followup, 8 patients died due to severe infection, 17 patients had doubling of serum creatinine, and 44 had end-stage renal disease. In multivariate analysis, male, elevated serum creatinine, and decreased hemoglobin were independently associated with poor renal outcomes. Conclusions. Renal TMA changes consisted of different disorders with various etiologies. aHUS, pregnancy-associated TMA, and malignant hypertension accounted for the majority of patients in our cohort.